Improving Vietnamese Law on Representative Worker Organisation as Vietnam Joins the Comprehensive and Progressive Agreement for Trans-Pacific Partnership - Thu, Le Thi Hoai (VNU Journal of Science: Legal Studies, 2018)
Representative worker organisation is an organisation that protects workers’ legitimate rights and interests. Workers’ rights to form and to join representative worker organizations at grassroots level should be respected and protected. This was affirmed by the parties to the Comprehensive and Progressive Agreement for Trans-Pacific Partnership through the labour commitments stipulated in Chapter 19 of CPTPP. This article points out the current legal provisions concerning representative worker organisation in Vietnam.The article concludes with recommendations to improve Vienamese law on representative worker organisation as Vietnam joins CPTPP. Keywords: Representative worker organisation, Trade Union, CPTPP. References: [1] Nguyễn Quang Quýnh, Luật lao động và An ninh xã hội, Sài Gòn, 1972. [2] Nguyễn Quang Quýnh, Giáo trình Luật - Lao động, chương trình cử nhân niên khoá 1974 - 1975, Sài Gòn, 1974. [3] Văn phòng lao động quốc tế, Tự do hiệp hội, Bộ tổng tập về các nguyên tắc và quyết định của Ủy ban ILO về tự do hiệp hội, Nxb. Lao động Xã hội, 6/2017. [4] Nghiên cứu về Việt Nam và cơ chế ba bên - Hà Nội, 1995 (Báo cáo của Dự án khu vực Châu Á - Thái Bình Dương về cơ chế ba bên do Na Uy tài trợ). [5] Trường Đại học Luật Hà Nội, Giáo trình Luật Lao động Việt Nam, Nxb. Công an Nhân dân, Hà Nội, 2009, Tr.147-148. [6] Bộ Lao động Thương binh và Xã hội, Báo cáo đánh giá 3 năm thực hiện Bộ luật Lao động, tháng 9/2016.